Management Leg Positioning After Total Knee Arthroplasty: An Evidence Based Nursing Practice - Adelina Vidya Ardiyati Adel; Debie Dahlia; Dikha Ayu Kurnia (International Journal of Nursing and Health Services (IJNHS), 2021)
Abstract. Total Knee Arthroplasty (TKA) is an effective surgical treatment in patients with moderate to severe knee arthritis. This surgical intervention has the potential to cause blood loss of up to 1000cc, which can lead to a decrease in haemoglobin levels and postoperative functional abilities. There are many methods to reduce the amount of blood loss after TKA surgery, one of the most effective and efficient methods is to position the knee flexion 45° for 24 hours post-operative TKA. This study was the application of Evidence Based Nursing (EBN) with a sample of 10 that meet theInclusion criteria were patients with knee osteoarthritis stage III and IV and underwent TKA Total Knee Arthroplasty (TKA) is an effective surgical treatment in patients with moderate to severe knee arthritis. This surgical intervention has the potential to cause blood loss of up to 1000cc, which can lead to a decrease in haemoglobin levels and postoperative functional abilities. There are many methods to reduce the amount of blood loss after TKA surgery, one of the most effective and efficient methods is to position the knee flexion 45° for 24 hours post-operative TKA. This case series aims to present the result of applying evidence-based leg positioning after TKA to reduce blood loss with a sample of 10 that meet the Inclusion criteria were patients with knee osteoarthritis stage III and IV and underwent TKA (Total Knee Arthroplasty) surgical procedures. The results show that all respondents are female, most of them are <60 years old (60%), and BMI in the overweight category is 70%, the amount of Hidden Blood Loss is in the range of 420cc-700cc, 30% of respondents have post-op Hb levels <10gr/dl, and 60% of respondents have a ROM value of 90° on day 5 Post Operation. The Implementation of EBN Knee flexion position for 24 hours post TKA effective to reduce the amount of blood loss and improve the patient's functional ability by facilitating the patient to start rehabilitation exercises early